Pertanian dan Irigasi Kolonial di Bone, 1911-1942 - Suardi, Suratman; Amir, Amrullah; Mappangara, Suriadi (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2023)
In the early decades of the 20th century, the Dutch East Indies government implemented the "ethical policy" in Bone. Bone was a potentially lucrative land that provided surplus growth to the economy, with the majority of its population relying on agriculture. The land was primarily managed by a rain-fed system, which presented opportunities for improving irrigation and increasing production. The purpose of this research is to understand how irrigation development supported agriculture in Bone between 1911 and 1942. The study employs historical methods consisting of heuristic, verification, interpretation, and historiography stages. The sources include documents, artifacts, newspapers, and magazines. The findings indicate that irrigation served as a transitional means of peace in the traditional-to-modern way of life for the community. Irrigation development was implemented gradually, from dam structures to canal channels, and built semi-permanently and permanently. Irrigation was intensively developed from 1920 to 1942 in Lerang, Maradda, Palakka, Pattiro, Palengoreng, Amali, Wolangi, Melle, Pacing, Bengo, Lanca, and Padang Lampe. These developments resulted in increased agricultural production and the export of crops through shipping and trading activities at Pallime, Bajoe, Ujung Pattiro and Barebbo ports.Dekade awal abad ke-20, pemerintah Hindia Belanda melaksanakan kebijakan politik etis di Bone. Bone merupakan lahan potensial yang memberikan surplus terhadap pertumbuhan ekonomi. Mayoritas masyarakatnya bergantung pada pertanian. Lahan yang dikelola didominasi sistem tadah hujan, memberikan peluang pendekatan tersedianya kebutuhan air dan peningkatan produksi. Tujuan penelitian ini untuk mengetahui pembangunan irigasi dalam menopang pertanian di Bone kurun tahun 1911-1942. Penelitian ini menggunakan metode sejarah, terdiri dari tahapan heuristik, verifikasi, interpretasi, dan historiografi. Sumber diperoleh berupa arsip, artefak, koran, dan majalah. Hasil penelitian menunjukkan irigasi menjadi sarana perdamaian transisi kehidupan masyarakat tradisional ke modern. Pembangunan irigasi dilaksanakan secara bertahap, dari bangunan bendung hingga saluran kanal, dan dibangun secara semi dan permanen. Irigasi dibangun secara intensif dari Kurun tahun 1920-1942, di Lerang, Maradda, Palakka, Pattiro, Palengoreng, Amali, Wolangi, Melle, Pacing, Bengo, Lanca, dan Padang Lampe. Pembangunan tersebut menunjukkan peningkatan hasil produksi dan ekspor hasil pertanian melalui kegiatan pelayaran dan perdagangan di pelabuhan Pallime, Bajoe, Ujung Pattiro dan Barebbo.